Factors Affecting Job Satisfaction at Ikan Bakar Jingkrak Restaurant Bandar Lampung - Safitri, Agung Ayu Tia; Rahayu, Ni Putu Widhia (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study was directed to determine the factors that determine employee job satisfaction at the Ikan Bakar Jingkrak restaurant. The study also investigated the effect of customer service training on job satisfaction, customer service rewards on job satisfaction, management styles on job satisfaction, and lastly job competence on job satisfaction. The study used quantitative methods. Data was collected through an online questionnaire using a Likert scale, a population of 35. The sampling technique used is saturated samples and uses Non Probability Sampling samples, data analysis using multiple linear tests with the help of SPSS version 25 and also hypothesis tests such as t tests and F tests.